A chemotherapy combined with an anti-angiogenic drug applied to a cancer model including angiogenesis. (June 2017) - Letellier, Christophe; Sasmal, Sourav Kumar; Draghi, Clément; Denis, Fabrice; Ghosh, Dibakar
Highlights: A combined therapy made of a chemotherapy and antiangiogenic agents and which is currently used in clinics is investigated. To test this combined therapy, a model taking into account the tumor micro-environment is used. The key parameter for the success of the treatment is the one driving the competition of host cells against tumor cells for oxygen and nutrients. As clinically observed, we show that increasing the dose of the drugs does not necessarily improve the survival. Abstract: Combined therapy made of a chemotherapy and antiangiogenic agents is a clinical treatment recommended for its efficiency. Since the optimization of a treatment against cancer relasp is still mostly based on oncologist's know-how, it is desirable to develop different approaches for such a task. Mathematical modelling is one of the promising ways. We here investigated the action of a combined therapy inserted to a mathematical cancer model in order to determine how the dynamics underlying tumor growth is governed by some key parameters. We here retained a chemotherapy (for instance, paclitaxel and carboplatin) combined with an antiangiogenic drug (as bevacizumab) applied to a cancer model describing the interactions between host, immune, tumor and endothelial cells. The effects of such a therapy are investigated and the relevant role played by the "normal" tissue of the tumor micro-environment is evidenced.